The Effect of Ginger Extract Concentration and Fermentation Time on the Decaffeination Process of Green Bean Robusta Coffee - Tri Hariyadi; Nurul Azka Saptajani; Shafira Nurul Aulia Zahra; Dhyna Analyes Trirahayu (Department of Chemical Engineering, Politeknik Negeri Bandung, 2025)
Decaffeination was performed using a fermentation method employing ginger crude extract containing the proteolytic enzyme zingibain. This study aimed to evaluate the effect of ginger crude enzyme concentration and fermentation time on the reduction of caffeine content in robusta coffee. Fermentation was conducted using ginger crude enzyme concentrations of 40, 50, 60, 70, 80, and 90% (v/v) and fermentation times of 6, 12, 18, 24, and 30 h. The optimum condition for caffeine reduction was obtained at 90% (v/v) ginger crude enzyme concentration and 30 h of fermentation. Organoleptic properties were evaluated by 30 untrained panelists. The results showed that ginger crude enzyme significantly affected the aroma, taste, and aftertaste of robusta coffee. This study demonstrates the potential of ginger crude enzyme fermentation as a natural alternative method for coffee decaffeination.